2014
DOI: 10.1111/1745-9125.12038
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Antisocial Behavior: The Mediating Role of Impulsive Sensation Seeking

Abstract: Although a low resting heart rate is considered the best-replicated biological correlate of antisocial behavior, the mechanism underlying this relationship remains largely unknown. Sensation-seeking and fearlessness theories have been proposed to explain this relationship, although little empirical research has been conducted to test these theories. This study addressed this limitation by examining the relationship between heart rate and antisocial behavior in a community sample of 335 adolescent boys. Heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 69 publications
4
72
3
Order By: Relevance
“…Zuckerman and others have long examined sensation seeking and impulsive behaviors' relation to criminal behavior and risky sexual behavior. In a study of 335 adolescent males and impulsive sensation seeking correlated significantly with violent antisocial behavior (r = .25), nonviolent antisocial behavior (r = .25) (Portnoy et al, 2014). Further, Gaither and Sellbom (2003) found moderate positive correlations between higher scores in sensation seeking and more one-night stands (r = .31), more partners in the last 3 months (r = .31), having a wider range of sexual experiences (r = .49), more frequent masturbation (r = .25), and engaging in vaginal intercourse at an earlier age among college students (r = ¡.31).…”
mentioning
confidence: 98%
“…Zuckerman and others have long examined sensation seeking and impulsive behaviors' relation to criminal behavior and risky sexual behavior. In a study of 335 adolescent males and impulsive sensation seeking correlated significantly with violent antisocial behavior (r = .25), nonviolent antisocial behavior (r = .25) (Portnoy et al, 2014). Further, Gaither and Sellbom (2003) found moderate positive correlations between higher scores in sensation seeking and more one-night stands (r = .31), more partners in the last 3 months (r = .31), having a wider range of sexual experiences (r = .49), more frequent masturbation (r = .25), and engaging in vaginal intercourse at an earlier age among college students (r = ¡.31).…”
mentioning
confidence: 98%
“…Recently, it has been found that of the two proposed explanations, sensation seeking appears to be the strongest mediator for the heart rate -antisocial behavior relationship. Portnoy et al (2014) showed that measures of impulsive sensation-seeking behavior explained around 36% percent of the total effect of heart rate on aggression and 27% percent of the effect of heart rate on non-violent delinquent behavior.…”
Section: Resting Heart Ratementioning
confidence: 99%
“…Owen et al 1996aOwen et al 1996b Furthermore, researchers should keep in mind that any test setting will be mildly stressful for most participants. Measuring heart rate prior to the beginning of an assessment might therefore contain a modest element of anticipatory anxiety (Portnoy et al 2014). For this reason, it is recommended to include more than one baseline measurement in the assessment and calculate the average heart rate over different baseline periods, or decide which measure best reflects a stress-free moment.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually overlapping with antisocial personality disorder and sociopathy (Mealey 1995), psychopathy is a highly heritable neurocognitive pattern (Blair et al 2005) eliciting exploitative, manipulative (Hare et al 1989), sensation seeking (Portnoy et al 2014), and Machiavellian (Paulhus and Williams 2002) behavior. Historically envisioned as a product of habitual abuse and poor attachment, there is, however, scant support for the causality of these environmental insults (Blair et al 2005).…”
Section: Personality Patterns and Life History Evolutionmentioning
confidence: 99%